Development, characterization and efficacy evaluation of dermocosmetic formulations based on a thermal water of Beira Interior of Portugal - Araújo, André (2015)
Portugal is one of the richest European countries in what concerns to thermal waters, and the majority of Portuguese spas are distributed by northern and central regions. The use of such water for therapeutic purposes, also known as mineral-medicinal water, has always been aroused a continuous interest in carrying out the characterization of this type of waters for the treatment of a specific condition. Many natural mineral waters are known for centuries for their dermatologic properties. Indeed, in the region of Beira Interior of Portugal, there is a spa with thermal water presenting dermatological therapeutic effects, named Termas do Cró, and therefore the incorporation of these thermal water in a cosmetic preparation will be a valuable tool. In the present work, it is aimed to develop cosmetic formulations based on a portuguese thermal mineral water, namely a gel, where it were carried out characterization and stabilities studies as well as the effects on the skin were evaluated through noninvasive biometric techniques, to demonstrate the potential of the vehiculation of thermal water in such systems. Furthermore, according to the therapeutic qualities exhibited by this thermal water and the developed dermocosmetic product, it could be also of great interest to use in specific dermatological diseases, like psoriasis and atopic dermatitis.